Flowpath Partitioning Controls Chemical Weathering Fluxes in the Tropics - William J. Larsen; Mark A. Torres; María Chapela Lara; Carla López Lloreda; William H. McDowell (Water Resources Research)
Abstract Tropical watersheds are thought to exert a strong control on the global carbon cycle because elevated temperature and rainfall rates promote the chemical weathering of silicate rocks. However, the critical factors that control tropical weathering, such as the role of subsurface flowpaths in setting the sensitivity of weathering to climate change, remain obscure. Here, we relate solute dynamics to flowpath partitioning using new and existing data from the Luquillo Critical Zone Observatory (LCZO) in the tropical forests of eastern Puerto Rico. We used new measurements of deuterium excess in streamflow and rainfall to show that the fraction of young water (Fyw, fraction of streamflow less than 1–3 months old) for each catchment increases with increasing discharge. We attribute Fyw‐Q behavior to the activation of shallow flowpaths that efficiently route incident rainfall to streamflow. Results from this 2‐year sampling period are comparable to results from end‐member mixing analysis of longer‐term solute records, suggesting that water routed via shallow flowpaths acquires little additional solutes from weathering reactions. Our findings of apparent mixing between flowpaths can be unified with time‐dependent weathering reactions and time‐variable transit time distributions. To estimate the response of the LCZO to climatic change, we compare Fyw‐Q behavior between sites that experience different mean annual precipitation amounts. Intriguingly, we find that climatically driven changes in flowpath partitioning reconcile watershed fluxes with regolith‐based studies. This suggests that shallow flowpath activation is the mechanism for maintaining constant weathering rates despite variable rainfall rates in the supply limited regions where weathering is already maximized.